Multi-omic insights into mitochondrial dysfunction and prostatic disease: evidence from transcriptomics, proteomics, and methylomics - Gong, Binbin; Yang, Feixiang; Zhang, Ning; Wu, Zhengyang; Liu, Tianrui; Wang, Kun; Zhang, Xiangyu; Zhang, Yangyang; Song, Zhengyao; Liang, Chaozhao (Frontiers in Genetics, 2025)
BackgroundProstatic diseases, consisting of prostatitis, benign prostatic hyperplasia (BPH), and prostate cancer (PCa), pose significant health challenges. While single-omics studies have provided valuable insights into the role of mitochondrial dysfunction in prostatic diseases, integrating multi-omics approaches is essential for uncovering disease mechanisms and identifying therapeutic targets.MethodsA genome-wide meta-analysis was conducted for prostatic diseases using the genome-wide association studies (GWAS) data from FinnGen and UK Biobank. Mitochondrial dysfunction-related genes were reviewed based on MitoCarta 3.0, with a library containing 1,244 mitochondrial genes. We integrated multi-omics through quantitative trait loci (QTL) across gene expression (eQTLs), protein abundance (pQTLs), and DNA methylation (mQTLs). We prioritized prostatic disease-related mitochondrial genes into three confidence tiers: Tier 1 (two eQTLs + pQTL + mQTL); Tier 2 (two eQTLs + pQTL/mQTL); and Tier 3 (eQTL + pQTL/mQTL). Further mediation analyses were performed to explore potential mediating pathways for the interaction between mitochondrial dysfunction and prostatic diseases, with 1,400 metabolomics and 731 immunomics.ResultsWe identified DCXR as the gene with Tier 1 evidence for BPH, validated by multi-omics integration through transcriptomic, proteomic, and methylomic signatures. We revealed two Tier 2 genes (NOA1 and ELAC2) and one Tier 3 gene (ACAT1) for BPH, two Tier 3 genes (TRMU and SFXN5) for prostatitis, and six Tier 3 genes (MRPL24, NDUFS6, PUS1, NBR1, GLOD4, and PCBD2) for PCa. We also explored the mediating pathways of mitochondrial genes (within the 3-tiers evidence) on prostatic diseases, and identified 8, 4, and 13 metabolites mediating the interaction between mitochondrial genes and BPH, prostatitis, and PCa, respectively, without the involvement of immune characters.ConclusionThese findings highlight the roles of mitochondrial dysfunction-related genes in prostatic diseases and identify key genes and pathways for potential therapeutic targets.